Left Ventricular Apical Aneurysm in a Dog—A Case Report - Ozana Maria Hritcu; Radu Andrei Baisan; Aurelian Sorin Pasca; Florentina Daraban Bocaneti (Animals)
The cadaver of a 16-year-old mixed-breed male dog was presented to the Faculty of Veterinary Medicine of IULS, Romania, after having been euthanized in a private practice at the owner’s request following acute cardio-respiratory failure. The necropsy revealed a left ventricular apical aneurysm with a bulging fibrous sac measuring about 0.7 cm/0.3 cm. The lesion involved all three structures of the cardiac wall, with mineralization areas and neovascularization. Immunohistochemistry showed strong positivity for desmin and weak positivity for CD-31 in the cardiac muscle fibers, positivity for α-sma in the smooth muscle cells of the vascular walls and positivity for vimentin in the cardiac stroma. MMP-2 and MMP-9 showed strong expression in the cardiomyocytes, whereas TIMP-1 showed positive immunoexpression only in the Eberth’s lines. To the authors’ knowledge, left ventricular apical aneurysm has only been reported once in dogs.